Distribution and composition of organic matter in sediments of the oxygen minimum zone of the Northeastern Mexican Pacific: paleoceanographic implications. - Sánchez, A.; López-Ortiz, B. E.; Aguíñiga-García, S.; Balart, E. (Journal of Iberian Geology, 2013)
Total organic carbon (TOC) content, total nitrogen (TN) content, elemental (C and N), and isotopic (d13C-TOC) composition of organic matter derived from both marine and terrestrial sources constrain the relative contributions from marine productivity, the mangroves, and the continental wind erosion of 36 carbonate-free surface sediments along the southwestern coast of the Baja California Peninsula. In general, the spatial patterns of TOC, TN, C:N ratio and d13C-TOC are similar. The maximum content of TOC (14.5%) and TN (1.6%) were measured inside the oxygen minimum zone (OMZ). The stable carbon isotopic compositions were enriched in 12C in surface sediments at suboxic sites within the OMZ. The C:N ratio and δ13C-TOC values indicated that the organic sediment material is predominantly of marine origin, with a minor contribution from the terrestrial source or mangroves. In the stations near to the coast, the high values of the C:N ratio and the depleted 13C values suggest a proportionally greater accumulation of terrestrial organic matter. The terrestrial-derived organic carbon content is <10% at the continental margin and >40% at the stations near to the coast, based on a Mixing Model of End Members.